Recurrent anticyclone formation and shedding within the Barreirinhas Bight (NE-Brazil) - Sousa, Iury Tercio Simoes de (2017)
The equatorial Brazilian margin is seen as a new frontier of mineral resources exploration, such as the Ceará and Barreirinhas oil-gas blocks. Nevertheless its economic relevance and contribution to heat and mass transport from south to north hemisphere, the North Brazil Current (NBC) and North Brazil Undercurrent (NBUC) has very few information in terms of its multiple retroflections and recirculations and the accompanying temporal variability. There is no report of the NBC/NBUC system between 0º-3ºS. The Barreirinhas Bight, from 0º-2ºS, has dimensions and similar bathymetric configuration to those of the Potiguar Bight. The Potiguar Eddy discovery invites to speculate whether similar vortical feature exists in the northern bight. We employed quasi-synoptic VMADCP and CTD data from Brazilian Navy\'s cruise Oceano Norte 1 (June 2001) and a current meter mooring data ceded by PETROBRAS (2007). In order to expand the analyses spatially and temporally, we use the velocity, salinity and temperature fields from global HYCOM simulation reanalysis named Experiment 19.1 (from 2001 to 2009). We describe the morphometric and dimensionless parameters for each observed feature as it time variability with mean fields and event statistics. The EOF analysis was used to investigate the vertical patterns of variability and its relation to vortical features within the bight. The NBC/NBUC jet recirculates and shed within Barreirinhas Bight two type of eddies, the near-surface (in TW domain) and the pycnoclinic (in SACW domain) eddy. The near-surfac Recorrente geração e propagação de anticiclones na Bacia de Barreirinhas (NE-Brasil) e (pycnoclinic) eddy has 100 m (150 m) of vertical extent and a cross-shore radius of about 35 km (80 km). The shallower one is anisotropic with a alongshore radius of 80 km. They both occur mainly from March to August typically as 7-day recurrent events with higher number of events in May. The EOF calculation revealed us that the dominant patterns of variability are associated with current inversions compatible with the eddy structures which vary importantly in the vertical. These eddies are not stationary and they propagate westward and are destroyed while leaving the equatorial border of the bight. With a Rossby and Richardson number of O(1), a aspect ratio of O(10-3) and a Burger number O(10)-O(10²), they are hydrostatic, submesoscale features with vortical dynamics governed by relative vorticity. This is the first study of the NBC/NBUC jet within the Barreirinhas Bight and, thus, it is the first description for the Barreirinhas Eddies.